1999
DOI: 10.1027//0227-5910.20.1.15
|View full text |Cite
|
Sign up to set email alerts
|

Common Risk Factors in Adolescent Suicide Attempters Revisited

Abstract: The principle risk factors for suicide attempts in adolescents discussed in the literature are examined on the basis of data from a study carried out at the Geneva University Hospitals. 148 adolescents aged between 15 and 19 years form the sample. The results concerning mental disorders at the time of the suicide attempt confirm the clear predominance of affective disorder as well as the elevated frequency of comorbidity. Other main risk factors include suicidal behavior in family members and among acquaintanc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

1999
1999
2016
2016

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(12 citation statements)
references
References 16 publications
0
11
0
Order By: Relevance
“…However, Grilo, Sanislow, Fehon et al, (1999b) found that adolescent inpatients with high levels of childhood abuse did have higher levels of suicide risk, even when controlling for depressive symptoms. Beautrais, Joyce, and Mulder (1996) and Laederach, Ladame, Fischer et al (1999) both also found that childhood sexual abuse increased the risk for suicide attempts.…”
Section: Clinic-and Hospital-based Studiesmentioning
confidence: 92%
See 1 more Smart Citation
“…However, Grilo, Sanislow, Fehon et al, (1999b) found that adolescent inpatients with high levels of childhood abuse did have higher levels of suicide risk, even when controlling for depressive symptoms. Beautrais, Joyce, and Mulder (1996) and Laederach, Ladame, Fischer et al (1999) both also found that childhood sexual abuse increased the risk for suicide attempts.…”
Section: Clinic-and Hospital-based Studiesmentioning
confidence: 92%
“…Several other hospital-based studies used cross-sectional samples (Grilo, Sanislow, Fehon et al, 1999a;Grilo, Sanislow, Fehon et al, 1999b;Laederach, Ladame, Fischer et al, 1999;Lipschitz, Hartnick, Wolfson et al, 1999;Lyon, Benoit, O'Donnell et al, 2000). The findings from these are somewhat mixed.…”
Section: Clinic-and Hospital-based Studiesmentioning
confidence: 99%
“…Eighty female patients aged between 15 and 20 years consulting a psychiatric outpatient service for adolescents in Geneva, Switzerland, were elected to participate in the study. The first subgroup consisted of 40 patients admitted to the emergency department of the Geneva University Hospital for attempted suicide and enrolled in a larger prospective outcome study of adolescent suicide attempts [10]. This first subgroup, characterized by suicide attempt (SA), was compared to 40 female patients who were referred to the Adolescent Psychiatry Unit having no history of suicide attempt (no attempt, NA).…”
Section: Methodsmentioning
confidence: 99%
“…This card enables the subject to show how his internal and external objects are structured and how he organizes these relationships. fragility in the individual, family, and contextual spheres (Brent, 2004;Laederach, Fischer, Bowen, & Ladame, 1999). In adolescence, narcissistic fragility is closely linked to the revival of oedipal conflict.…”
Section: Prevalence Of "Penetration" Indices After the Suicidal Act: mentioning
confidence: 99%